Role of Resilience to Improving the Performance of Health Workers: A Systematic Review - Handini, Febrina Secsaria; Kusnanto, Kusnanto; Yuswanto, Tri Johan Agus (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This systematic review is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The databases used in this study include Scopus, Science Direct, PubMed, and Pro Quest, limited to publications from 2016 to 2020 and full-text articles. The keywords used are "healthcare" AND "Resilience" AND "job performance" OR "work performance". This systematic review uses 12 articles that fit the inclusion criteria. This systematic review proves the role of resilience in improving the job performance of healthcare. There are eleven out of twelve studies that prove that resilience directly has a positive and significant correlation to the performance. In addition to playing a direct role, resilience also acts as a mediator both in full and in part between other independent variables with performance. Further research can be done in the form of developing resilience-based performance models as an effort to increase the productivity of nurses in Indonesia